Dīmukrātīyah fī al-Sirā’i al-Fikrī al-Islāmī fī Indūnīsīyā - Syukron Kamil (Studia Islamika, 2007)
In 1998 Indonesia entered what has become known as the Reformation era, a period defined by the relative dominance of democratic ideas and practices, both in the socio-political sense and the religious sense. This piece of writing retraces the ideological struggle of prominent Indonesian Muslim figures to bring democracy to lndonesia, a struggle which began in the 1980s. In this way, this article endeavors to respond to the critics and doubters - like Larry Diamond and Juan Linz - who believe that the ideals of democracy conflict with those of Islam and thus argue that the two cannot co-existDOI: 10.15408/sdi.v14i3.549